Sexual Orientation, Controversy, and Science. (September 2016) - Bailey, J. Michael; Vasey, Paul L.; Diamond, Lisa M.; Breedlove, S. Marc; Vilain, Eric; Epprecht, Marc
Summary: Ongoing political controversies around the world exemplify a long-standing and widespread preoccupation with the acceptability of homosexuality. Nonheterosexual people have seen dramatic surges both in their rights and in positive public opinion in many Western countries. In contrast, in much of Africa, the Middle East, the Caribbean, Oceania, and parts of Asia, homosexual behavior remains illegal and severely punishable, with some countries retaining the death penalty for it. Political controversies about sexual orientation have often overlapped with scientific controversies. That is, participants on both sides of the sociopolitical debates have tended to believe that scientific findings—and scientific truths—about sexual orientation matter a great deal in making political decisions. The most contentious scientific issues have concerned the causes of sexual orientation—that is, why are some people heterosexual, others bisexual, and others homosexual? The actual relevance of these issues to social, political, and ethical decisions is often poorly justified, however.